Measurement of the integrated and differential t¯tproduction cross sections for high-pT top quarks in ppcollisions at ?s=8??TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Ero, J.; Flechl, M.; Friedl, M.; et al. (My University, 2016)
The cross section for pair production of top quarks (t (t) over bar) with high transverse momenta is measured in pp collisions, collected with the CMS detector at the LHC with root s = 8 TeV in data corresponding to an integrated luminosity of 19.7 fb(-1). The measurement is performed using lepton + jets events, where one top quark decays semileptonically, while the second top quark decays to a hadronic final state. The hadronic decay is reconstructed as a single, large-radius jet, and identified as a top quark candidate using jet substructure techniques. The integrated cross section and the differential cross sections as a function of top quark pT and rapidity are measured at particle level within a fiducial region related to the detector-level requirements and at parton level. The particle-level integrated cross section is found to be sigma t (t) over bar = 0.499 + 0.035 (stat + syst) +/- 0.095 (theo) + 0.013 (lumi) pb for top quark p(T) > 400 GeV. The parton-level measurement is sigma t (t) over bar = 1.44 +/- 0.10 (stat + syst) + 0.29 (theo) + 0.04 (lumi) pb. The integrated and differential cross section results are compared to predictions from several event generators.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Collaboration, C. M. S. (2016). Measurement of the integrated and differential t(t)over-bar production cross sections for high-p(T) top quarks in pp collisions at root s=8 TeV. Physical Review D, 94(7), 25. doi:10.1103/PhysRevD.94.072002
Keywords: Parton Distributions; Lhc; Astronomy & Astrophysics; Physics